Letters to the Media of October 20, 2017 - Szczęsny, Piotr; Konior, Bogna M. (Identities: Journal for Politics, Gender and Culture, 2018)
Along with the leaflet, Piotr Szczęsny wrote two short letters, referred to as “Letters to the Media.” They were handed over by Szczęsny’s family to the major media outlets and published on October 20, 2017. The translation is based on the original publication in Oko.Press, October 20, 2017, www.oko.press/piotr-s-szary-czlowiek-zyje-czescpamieci. Author(s): Piotr Szczęsny Title (English): Letters to the Media of October 20, 2017 Translated by (Polish to English): Bogna M. Konior Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 164-165 Page Count: 2 Citation (English): Piotr Szczęsny, “Letters to the Media of October 20, 2017,” translated from the Polish by Bogna M. Konior, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 164-165.